(untitled) (Balneo and PRM Research Journal, 2022)
The purpose of the present study is to compare the efficiency of two physiotherapeutic programs for rehabilitation of the lower limbs, one using a stationary bicycle and the other one being a standard program, targeting muscle imbalance deficit. Subjects are outpatients - the control group (C n=5), 58.67 ± 11.67 years, received a standard rehabilitation program, and the experimental group (E n=5), 56.67 ± 12.14 years, received a proposed rehabilitation program implying a stationary bicycle. Equipment used is for muscle imbalances – sensor attached to bicycle pedals, for joint testing – goniometer, for heart rate smart watch, pain assessment – VAS numeric scale, and for perceived effort Borg scale. The rehabilitation program including the stationary horizontal bicycle obtained better results in terms of pain control (T-Test p C/E=.004/.001 and Wilcoxon p C/E=.039/.041) and the correction of muscular imbalances (T-Test p C/E=.003/.000, r= .990/.997) related to the lower limbs, with the mention that both programs recorded statistically significant results regarding functionality. HR values for the control group and experimental group < THR values, aerobic conditioning with the submaximal effort being essential for rehabilitation. Both programs maintained the same perceived level of effort with an average of 3.6 Borg- moderate effort, respectively mild-moderate dyspnea.